The "humane in the loop": Inclusive research design and policy approaches to foster capacity building assistive technologies in the COVID-19 era. - Bricout, John; Greer, Julienne; Fields, Noelle; Xu, Ling; Tamplain, Priscila; Doelling, Kris; Sharma, Bonita (Assistive Technology, 2022)
The COVID-19 pandemic is emerging as a driver of greater reliance on wireless technologies, including intelligent assistive technologies, such as robots and artificial intelligence. We must integrate the humane "into the loop" of human-AT interactions to realize the full potential of wireless inclusion for people with disabilities and older adults. Embedding ethics into these new technologies is critical and requires a co-design approach, with end users participating throughout. Developing humane AT begins with a participatory, user-centered design embedded in an iterative co-creation process, and guided by an ethos prioritizing beneficence, user autonomy and agency. To gain insight into plausible AT development pathways ("futures"), we use scenario planning as a tool to articulate themes in the research literature. Four plausible scenarios are developed and compared to identify one as a desired "humane" future for AT development. Policy and practice recommendations derived from this scenario, and their implications for the role of AT in the advancement of human potential are explored.